UNEMPLOYMENT OF VOCATIONAL HIGH SCHOOL GRADUATES: THE EFFECT OF WORK SKILLS, FAMILY SOCIO-ECONOMIC STATUS, AND ENTREPRENEURIAL ATTITUDES ON WORK READINESS - Agussalim, Agussalim; Mukhlis, Imam; Rohayati, Suci; Wahyuni, Wahyuni; Said, Sitaman (UNIVERSITAS NEGERI SURABAYA, 2024)
The aim of this research is to examine the impact of work skills and family socio-economic status on work readiness, with entrepreneurial attitude as an intervening variable for Vocational High School graduates. A total of 179 graduates of Bima State Vocational School were the research sample, using a non-probability sampling approach, specifically for graduates from 2015 to 2022 who had not worked in their field of expertise for more than one year. The questionnaire instrument was designed based on research variables to collect research data. Data analysis uses Structural Equation Modeling (SEM). The results indicate that both work skills and family socioeconomic status do not play a substantial role in determining work readiness. On the other hand, having an entrepreneurial mindset has a noteworthy and positive effect on work readiness. Furthermore, it was observed that job skills and family socioeconomic status indeed influence work readiness, with entrepreneurial attitude serving as a key factor. The entrepreneurial mindset heavily shapes the work readiness of vocational high school graduates. Hence, the vocational education curriculum must emphasize the development of entrepreneurial attitudes and work readiness.